ANALISIS KONTEN VIDEO RUANG GURU PADA MATERI USAHA, ENERGI, DAN PESAWAT SEDERHANA IPA KELAS 8: TINJAUAN KURIKULUM DAN PEDAGOGIS - Adesta Friza Sandyka; Hendra Febriyanto (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
The utilization of e-learning platforms such as Ruang Guru in Natural Sciences (IPA) learning is becoming increasingly massive; however, the abundance of content does not always guarantee academic quality and alignment with curriculum standards. This research aims to analyze the feasibility of Ruang Guru's instructional video content on Work, Energy, and Simple Machines for 8th-grade junior high school students, reviewed from curricular and pedagogical aspects. This study employed a mixed methods approach with a concurrent design, combining qualitative content analysis of 10 videos, validation by four experts, and a quantitative survey of 23 students. The assessment covered three aspects: the feasibility of content and curriculum, pedagogical aspects, as well as visual and media presentation. The results showed that the overall feasibility level of the videos reached 71.94% (Feasible). The visual and media aspect achieved the highest score (10.7 out of 12; Very Feasible) due to the effective use of motion graphics in visualizing abstract physics concepts, supported by highly positive responses from students and experts. Conversely, the pedagogical aspect received the lowest score (7 out of 12; 58.33%) reflecting the dominance of one-way instruction (direct instruction) that lacks facilitation for higher-order thinking skills (HOTS) and independent inquiry. In conclusion, Ruang Guru videos are feasible to be used as introductory media for basic science concepts, but their classroom application still requires teacher guidance to facilitate critical discussion and deeper problem-solving. ABSTRAK Pemanfaatan platform e-learning seperti Ruang Guru dalam pembelajaran Ilmu Pengetahuan Alam (IPA) semakin masif, namun melimpahnya konten tidak selalu menjamin kualitas akademis dan kesesuaian dengan standar kurikulum. Penelitian ini bertujuan menganalisis kelayakan konten video Ruang Guru materi Usaha, Energi, dan Pesawat Sederhana kelas VIII SMP, ditinjau dari aspek kurikulum dan pedagogis. Penelitian ini menggunakan metode mixed methods dengan desain konkuren, yang menggabungkan analisis konten kualitatif pada 10 video, validasi oleh empat ahli, dan survei kuantitatif terhadap 23 siswa. Penilaian mencakup tiga aspek: kelayakan isi materi dan kurikulum, pedagogis, serta tampilan visual dan media. Hasil penelitian menunjukkan tingkat kelayakan video secara keseluruhan mencapai 71,94% (Layak). Aspek tampilan visual dan media meraih skor tertinggi (10,7 dari 12; Sangat Layak) berkat penggunaan motion graphic yang efektif memvisualisasikan konsep fisika abstrak, didukung respons sangat positif dari siswa dan ahli. Sebaliknya, aspek pedagogis mendapat skor terendah (7 dari 12; 58,33%) akibat dominasi instruksi satu arah (direct instruction) yang kurang memfasilitasi kemampuan berpikir tingkat tinggi (HOTS) dan inkuiri mandiri. Kesimpulannya, video Ruang Guru layak digunakan sebagai media pengantar konsep dasar IPA, namun penerapannya di kelas tetap membutuhkan bimbingan guru untuk memfasilitasi diskusi kritis dan pemecahan masalah yang lebih mendalam.